2018
DOI: 10.1111/eos.12398
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between enamel bond fatigue durability and surface free‐energy characteristics with universal adhesives

Abstract: The relationship between enamel bond fatigue durability and surface free-energy characteristics with universal adhesives was investigated. The initial shear bond strengths and shear fatigue strengths of five universal adhesives to enamel were determined with and without phosphoric acid pre-etching. The surface free-energy characteristics of adhesive-treated enamel with and without pre-etching were also determined. The initial shear bond strength and shear fatigue strength of universal adhesive to pre-etched en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Statistical analysis was conducted as described by Nagura et al [18], with the exception that Fisher's exact test was not used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analysis was conducted as described by Nagura et al [18], with the exception that Fisher's exact test was not used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the first null hypothesis that etching mode would make no difference to the bond fatigue resistance of universal adhesives to dentin was not rejected. A recent study [18], which uses the same research design to study bonding to enamel, has reported that the bond fatigue resistance of universal adhesives was significantly higher in etch-and-rinse than in self-etch mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the variation in resistance against acid dissolution of prismatic and aprismatic enamel leads to different etching pattern. Enamel pre-etching with phosphoric acid removes the smear layer, changing the surface properties and increases the wettability of enamel surface, by exposing the hydroxyl groups of the enamel, therefore producing a consistent enamel etching pattern [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…After establishing these basic principles, the research group extended fatigue bond strength evaluations to cover many factors with an influence on tooth bonding, such as the influence of acidic functional monomers [34] , double coating [35] , the oxygen inhibition layer [36] , [37] , shortened application times of adhesive systems [38] , the etching mode for universal adhesives [39] , [40] , [41] , application of different etching agents [42] , [43] , [44] , [45] , silver diamine fluoride pre-treatment [46] , the prismatic structure of enamel [47] , surface moisture [48] or smear layer of substrates [49] , the use of different adhesive systems [50] , [51] , phosphoric acid pre-etching [52] , [53] , [54] , self-adhesive restorative materials [55] , short fiber resin composites [56] , and water storage of specimens [57] . These evaluations did provide new insights, but also raised methodological suggestions and questions from researchers.…”
Section: Standardization Of Test Conditionsmentioning
confidence: 99%